2014
DOI: 10.1371/journal.pcbi.1003583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Filtering Methods for the Modeling and Retrospective Forecasting of Influenza Epidemics

Abstract: A variety of filtering methods enable the recursive estimation of system state variables and inference of model parameters. These methods have found application in a range of disciplines and settings, including engineering design and forecasting, and, over the last two decades, have been applied to infectious disease epidemiology. For any system of interest, the ideal filter depends on the nonlinearity and complexity of the model to which it is applied, the quality and abundance of observations being entrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
191
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(204 citation statements)
references
References 28 publications
(64 reference statements)
1
191
0
1
Order By: Relevance
“…With regard to seasonal influenza, existing forecasting studies have focused on cities across the USA, but as Yang et al . state, ‘the performance of any filter may be application dependent’ 11. The results presented here are the first application of such forecasting methods to Australian data and demonstrate that we are able to obtain similar forecasting accuracy in the Australian context.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…With regard to seasonal influenza, existing forecasting studies have focused on cities across the USA, but as Yang et al . state, ‘the performance of any filter may be application dependent’ 11. The results presented here are the first application of such forecasting methods to Australian data and demonstrate that we are able to obtain similar forecasting accuracy in the Australian context.…”
Section: Discussionmentioning
confidence: 55%
“…A recent comparison of filtering methods for influenza epidemic forecasting (applied to 115 cities in USA) found that the peak timing forecasts were comparably accurate for the six surveyed methods 11. It was also observed that the particle filters performed ‘slightly better predicting peaks 1–5 weeks in the future’, while ‘ensemble [Kalman] filters were better at indicating that the seasonal peak had already occurred’.…”
Section: Methodsmentioning
confidence: 99%
“…S, E, I, for each district) and model parameters, including the transmission rate b for each district, the incubation period, the infectious period and the three exponents (t 1 , t 2 and r) for the gravity model. The EAKF [15,23,[25][26][27]] is a data assimilation method that uses an ensemble of system replicas to represent the distribution of possible model state and parameter values. It approximates a Bayesian update to the model states and parameters using the observational data and an estimate of the errors in the data.…”
Section: Framework Of the Spatio-temporal Inference Systemmentioning
confidence: 99%
“…One could, for example, modify IF2 to use an ensemble Kalman filter (20,34) or an unscented Kalman filter (35). Or, one could take advantage of variations of sequential Monte Carlo that may improve the numerical performance (36).…”
Section: Discussionmentioning
confidence: 99%